A cross-lagged analysis of the relationship between short video overuse behavior and depression among college students - Zhang, Dongning; Yang, Yifu; Guan, Muzhen (Frontiers in Psychology, 2024)
Introduction: Watching short videos on mobile phones is currently a very prevalent phenomenon. It has been found in research that excessive use of short videos is closely related to depression. The aim of this study is to investigate the relationship between short video overuse behavior and depression among college students as well as the gender differences that are present in such relationship.Methods: A follow-up measurement was conducted on 331 college students using the Short Video Usage Behavior Scale and the Epidemic Research Center Depression Scale with an interval of two months. Results: (1)Correlation analysis revealed a significant positive correlation between short video overuse behaviour and depression, whether measured at the same or different time points, Repeated measures analysis of variance indicates that short video overuse behavior and depression have strong stability within the interval between two measurements. (2)Pre-test short video overuse behaviour could significantly and positively predict post-test depression, whereas pre-test depression could not significantly predict post-test short video overuse behaviour. (3) The cross-lagged effect between short video overuse behaviour and depression showed no gender differences. Discussion:These findings indicate that, for college students, short video overuse behaviour may increase the risk of depression, whereas depression cannot induce short video overuse behaviour.